The comparison of the effect of game and motion-based gross motor skills training programmes on the 4-5 year-old children's gross motor skills - Kezban Tepelı; Nurcan Kocak; Ozgur Gul (Selcuk University, 2014)
The aim of the study was to analyze the effects of the large muscle skills-education programs based on game and movement on the large muscle skills in children aged between 4-5. The study group totally consisted of 65 children including 22 ones (game) for the experimental group 1, 22 ones (movement) for the experimental group 2 and 21 ones for the control group, who went to the kindergarten in this study process. The experimental model with pretest and final test control groups was used in the research. A 12-week education was given to the children in the experimental group 1 and the experimental group 2 for 45 minutes during two days on average, but the control group was not given any education. Skills determined in education given to the children were presented to the game group with an education programme based on game whereas these were given to the movement group with an education programme based on movement. The children's large muscle skills were evaluated by the Measurement Test for Large Muscle Skills (BÜKBÖT). BÜKBÖT regarded the children's large muscle skills as the overall point, their locomotor skills and object control skills as the subtest point. As a consequence, it was found that the applications regarding the Large Muscle Skill-Education Programs Based on Game and Movement developed children aged 4-5 in a positive way but the Large Muscle Skill-Education Program Based on Game was more effective on children in this age group.